Predictors of frontal plane knee excursion during a drop land in young female soccer players - Sigward, S. M.; Ota, S.; Powers, C. M. (Journal of Orthopaedic & Sports Physical Therapy, 2008)
Study design: Controlled laboratory study using a cross-sectional, single testing session. Objective: To determine the association between frontal plane knee excursion during a drop land task and measures of hip strength, and ankle and hip range of motion. Background: Assessment of frontal plane knee excursion during a drop land task has been advocated as a means to screen for potentially injurious lower extremity movement patterns. Accordingly, an understanding of the physical characteristics associated with the magnitude of frontal plane knee excursion could assist clinicians in developing interventions and prevention strategies to minimize injury risk. Methods and measures: Thirty-nine female high school soccer players (mean ± SD age, 15.5 ± 1.0 years; height, 162.2 ± 5.3 cm; body mass, 56.8 ± 6.7 kg) participated. Isometric hip muscle strength as well as ankle and hip range of motion measurements were obtained using standard clinical procedures and a handheld dynamometer. Frontal plane knee excursion was assessed using a 6-camera motion analysis system during a drop land task. Using 3-dimensional coordinate data, maximum frontal plane knee excursion was defined as the difference between the distances of right and left lateral knee markers at initial contact and maximum knee flexion during the deceleration phase of landing. Independent variables found to be significantly correlated with frontal plane knee excursion were then entered into a stepwise multiple regression procedure to determine the best set of predictors of this motion. Results: Hip external rotation range of motion and ankle dorsiflexion range of motion were found to be negatively correlated with frontal plane knee excursion (r=-0.40, P=.005 and r=-0.27, P=.05, respectively). Together they accounted for 27% of the variance in frontal plane knee excursion (r=0.52, P=.03). No relationships between measures of hip strength and frontal plane knee excursion were found. Conclusions: Frontal plane knee excursion during a drop land task was partially attributed to available range of motion at the hip and ankle. These results suggest that range of motion of the joints proximal and distal to the knee should be considered when evaluating individuals who present with excessive frontal plane knee excursion during this task. Given that the relationship between range of motion and frontal plane knee excursion was small, other factors, including learned motor patterns, should be considered.